(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This article describes the Spanish economic crisis through an analysis of the main macroeconomic aggregates (Gross Domestic Product, consumers’ expenditure, grossdomestic fixed capital formation, exports and imports, etc.) and analyzes endogenousand exogenous determining factors. Among the endogenous factors, we highlight thein adequate pattern of expenditure of the Spanish economy that has generated significant imbalances between expenditure and output, investment and savings, and imports and exports and a high level of indebtedness by firms and households. Among the exogenous factors we highlight the international financial crisis as the result of aset of factors such as, the irresponsible behaviour of financial intermediaries, a poor regulation and supervision of the financial sector and an over expansionary monetary policy applied by the US Federal Reserve. Then, we examine possible economic policy measures to confront the Spanish economic crisis. To conclude, the article reviews the principal economic policy measures adopted by the Spanish Government.